Aporofobia, marginación y ex(in)clusión en la realidad sociopolítica de la España actual: Silencio administrativo y Un incendio invisible, de Sara Mesa - Kobiela-Kwaśniewska, Marta (Studia Romanica Posnaniensia, 2026)
This study examines aporophobia, gerontophobia and social discrimination in Sara Mesa’s novel Un incendio invisible and in her essay Silencio administrativo, interpreting the experiences of the marginalized main characters by means of various academic approaches including those of Bauman, Myrdal, Lipovetsky, and Cortina in order to understand the social dimension of marginalization and promote more inclusive practices. The study argues that, despite their different aesthetics, Mesa’s selected works function as a critique of the economic aftermath of the 2008 Spanish financial crisis.